Polyclonal antibody production anti Pc_312-324 peptide: Its potential use in electrochemical immunosensors for transgenic soybean detection - Farias, Marcos Ezequiel (2020)
A new polyclonal antibody that recognizes the CP4 5-enolpyruvylshikimate-3-phosphate synthase (CP4-EPSPS), which provides resistance to glyphosate in soybean (Roundup Ready®, RR soybean), was produced. New Zealand rabbits were injected with a synthetic peptide (Pc_312-324, (PEP)) present in the soybean CP4-EPSPS protein. The anti-PEP antibodies production was evaluated by electrophoresis (SDS-PAGE) and an enzyme-linked immunosorbent assay (ELISA) was developed in order to study their specificity. The ELISA showed that the polyclonal antibody was specific to PEP. In addition, the anti- PEP was immobilized onto a gold disk electrode and the antigen-antibody interaction was evaluated using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Moreover, the EIS showed that the electron transfer resistance of the modified electrode increased after incubation with solutions containing CP4-EPSPS protein from RR transgenic soybean, while no changes were detected after incubation with no-RR soybean proteins. These results suggest that the CP4-EPSPS was immobilized onto the electrode, due to the specific interaction with the anti-PEP. These results show that this antigen-antibody interaction can be detected by electrochemical techniques, suggesting that the anti-PEP produced can be used in electrochemical immunosensors development to quantify transgenic soybean.